De alveitares a veterinários: notas históricas sobre a medicina animal e a Escola Superior de Medicina Veterinária São Bento de Olinda, Pernambuco (1912-1926) From animal medical practitioners to veterinarians: historical note on animal medicine and the São Bento de Olinda Graduate School of Veterinary Medicine, Pernambuco (1912-1926) - Lúcio Esmeraldo Honório de Melo; Francisco de Oliveira Magalhães; Argus Vasconcelos de Almeida; Cláudio Augusto Gomes da Câmara (História, Ciências, Saúde: Manguinhos, 2010)
Os aspectos históricos da medicina animal, examinados mediante revisão de literatura indicam ruptura epistemológica, com as antigas práticas de alveitaria, com introdução dos princípios de racionalidade, a partir do século XVIII, na formação dos médicos-veterinários. Essas práticas curativas, entretanto, não começaram com a implementação dos cursos superiores de medicina animal. No Brasil colonial e particularmente em Pernambuco ocorrem registros históricos de práticas alveitares, mais tarde incorporadas ao currículo da Escola Superior de Medicina Veterinária São Bento de Olinda, pela existência de avaliação única no Brasil: o exame physicum. The historical aspects of animal medicine indicate an epistemological break with the old practices of animal medical treatment, with introduction of the principles of rationality in the eighteenth century in the formation of veterinary doctors. These healing practices, meanwhile, did not begin with the implementation of graduate courses in animal medicine. In colonial Brazil and, in particular, in the State of Pernambuco, historical records can be found of animal medical practices that were later incorporated into the curriculum of the São Bento de Olinda Graduate School of Veterinary, marked by the presence of a unique evaluation in Brazil: the physicum examination.